2016
DOI: 10.1093/schbul/sbw083
|View full text |Cite
|
Sign up to set email alerts
|

Joint Effects of Exposure to Prenatal Infection and Peripubertal Psychological Trauma in Schizophrenia

Abstract: Context: Prenatal infection and traumatizing experiences have both been linked with schizophrenia, but none of these factors seem sufficient to cause the disorder. However, recent evidence suggests that these environmental insults act in synergy to increase schizophrenia risk. Objective: To estimate the independent and joint effects of exposure to prenatal infection and peripubertal psychological trauma on the risk of schizophrenia. Design: Danish nationwide registers were linked in this prospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 50 publications
4
46
0
Order By: Relevance
“…Preliminary evidence from research in mice suggests that combined exposure to prenatal inflammation and postnatal psychological stress in adolescence is associated with behavioral and neurochemical abnormalities consistent with those seen in neuropsychiatric disorders, highlighting the possibility of synergistic environment factors in the development of psychopathology (Giovanoli et al, 2013, 2014). A recent study in humans provides similar support, finding joint effects of exposure to prenatal infection and offspring psychological trauma in the development of schizophrenia (Debost et al, 2017). Such findings imply that prenatal exposure to maternal environmental factors, such as prenatal stress and infection, may influence fetal growth and development, resulting in long-term health consequences for offspring.…”
Section: Discussionmentioning
confidence: 60%
“…Preliminary evidence from research in mice suggests that combined exposure to prenatal inflammation and postnatal psychological stress in adolescence is associated with behavioral and neurochemical abnormalities consistent with those seen in neuropsychiatric disorders, highlighting the possibility of synergistic environment factors in the development of psychopathology (Giovanoli et al, 2013, 2014). A recent study in humans provides similar support, finding joint effects of exposure to prenatal infection and offspring psychological trauma in the development of schizophrenia (Debost et al, 2017). Such findings imply that prenatal exposure to maternal environmental factors, such as prenatal stress and infection, may influence fetal growth and development, resulting in long-term health consequences for offspring.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, there is currently not an effective way to identify the at-risk pregnancies. The majority of pregnancies even at high risk will lead to healthy offspring and the resulting CNS disorders in offspring often do not appear for many years after birth and appear to be influenced by postnatal risk factors that synergize with genetic and prenatal risk to act as “second hits”(3, 1315). Clearly, there is a compelling need for long-term and large prospective studies to identify the specific aspects of infection during pregnancy (the type of pathogen, extent of fever, timing of infection, etc.…”
Section: Animal Models Of Maternal Infectionmentioning
confidence: 99%
“…We have initially identified a specific miRNAs signature associated with stress exposure in different species and tissues, which were: i) peripheral blood of human controls exposed to childhood trauma as compared to controls who did not experience such stressful events; ii) hippocampus of PNS rats as compared with non- (Abbott et al, 2018;Malarbi et al, 2017) and suggest that stressful experiences, especially early in life, can affect neurodevelopmental and inflammatory-related systems, rendering stressed individuals more vulnerable to a further second stressful challenge (Debost et al, 2017;Giovanoli et al, 2013) and thus more vulnerable to develop a stress-related psychiatric disorder. Moreover, in our recent paper, we have demonstrated that FoxO1 is a novel potential candidate gene able to mediate the effect of stress early in life on the future vulnerability of developing a psychopathology (Cattaneo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%